2014
DOI: 10.1038/ismej.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics of two environmentally relevant cyanobacteria reveals unexpected transcriptome diversity

Abstract: Prochlorococcus is a genus of abundant and ecologically important marine cyanobacteria. Here, we present a comprehensive comparison of the structure and composition of the transcriptomes of two Prochlorococcus strains, which, despite their similarities, have adapted their gene pool to specific environmental constraints. We present genome-wide maps of transcriptional start sites (TSS) for both organisms, which are representatives of the two most diverse clades within the two major ecotypes adapted to high-and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 59 publications
5
71
0
Order By: Relevance
“…Differential expression (DE) analysis was performed using the Rockhopper program (McClure et al, 2013). Similar to previous studies (Waldbauer et al, 2012;Voigt et al, 2014), we observed antisense expression in most of the genes (766/1716 genes in MED4 and 2060/2274 genes in MIT9313). Little is currently known about the function of these antisense RNAs, and thus we focused our analysis on protein-coding genes.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Differential expression (DE) analysis was performed using the Rockhopper program (McClure et al, 2013). Similar to previous studies (Waldbauer et al, 2012;Voigt et al, 2014), we observed antisense expression in most of the genes (766/1716 genes in MED4 and 2060/2274 genes in MIT9313). Little is currently known about the function of these antisense RNAs, and thus we focused our analysis on protein-coding genes.…”
Section: Methodssupporting
confidence: 84%
“…However, many of the predicted CCRG-2 core peptides do not contain cysteine residues and thus cannot be modified by the ProcM enzyme to form the lanthionine ring that is one of the hallmarks of lanthipeptides (Figure 5e). Notably, in some prochlorosin genes, transcription may start downstream of the predicted open reading frame, leading to translated proteins which lack much of the N'-terminal leader sequence (Voigt et al, 2014). It is unclear whether these truncated prochlorosins can be recognized and modified by the ProcM enzyme.…”
Section: Transcriptome Of Prochlorococcus In Co-culture D Aharonovichmentioning
confidence: 99%
“…After 48 h, both the NrdR transcription factor (involved in regulating ribonucleotide reductase expression (Torrents et al, 2007)) and a putative AbrB-family regulator were both transcriptionally enriched in the co-cultures, and a putative GntR-like transcription factor was found to be depleted after 24 h (Supplementary Table S2). Antisense RNAs have an important role in Prochlorococcus transcriptional regulation (Steglich et al, 2008;Voigt et al, 2014), and while they have not yet been characterized in this particular strain, we expect that they likely contributed to at least some of the changes observed.…”
Section: Regulation Of Transcriptional Responses To Co-culturementioning
confidence: 93%
“…Indeed, for many microbial populations, functional activity is regulated at the transcriptional level, so there is a strong relationship between transcripts and functionality. Furthermore, noncoding RNA is emerging as a major component of functional regulation, thus providing significant insight into physiological diversity (Voigt et al 2014). However, other functions-and, in particular, many functions associated with eukaryotic phytoplankton species-are not necessarily regulated at the transcriptional level, so care must be taken in interpretation.…”
Section: Figurementioning
confidence: 99%